Hallucinogen use predicts reduced recidivism among substance-involved offenders under community corrections supervision. (January 2014) - Hendricks, Peter S; Clark, C Brendan; Johnson, Matthew W; Fontaine, Kevin R; Cropsey, Karen L
Hallucinogen-based interventions may benefit substance use populations, but contemporary data informing the impact of hallucinogens on addictive behavior are scarce. Given that many individuals in the criminal justice system engage in problematic patterns of substance use, hallucinogen treatments also may benefit criminal justice populations. However, the relationship between hallucinogen use and criminal recidivism is unknown. In this longitudinal study, we examined the relationship between naturalistic hallucinogen use and recidivism among individuals under community corrections supervision with a history of substance involvement ( n =25, 622). We found that hallucinogen use predicted a reduced likelihood of supervision failure (e.g. noncompliance with legal requirements including alcohol and other drug use) while controlling for an array of potential confounding factors (odds ratio (OR)=0.60 (0.46, 0.79)). Our results suggest that hallucinogens may promote alcohol and other drug abstinence and prosocial behavior in a population with high rates of recidivism.